Activated Carbon Fixed-Bed Adsorber Design for Treating Chromium Hexavalent Wastewater - Hudaya, Tedi; Rachmat, Velicia (Makara Journal of Technology, 2018)
Pollution caused by industrial wastewater containing heavy metals is a major issue, primarily due to its toxic nature. A cheap yet effective method to deal with such wastewater is activated carbon adsorption. The purpose of this research is to evaluate and design a fixed bed adsorber with granular activated carbon as an adsorbent to process wastewater-containing chromium hexavalent (Cr 6+). Experiments show that the Langmuir isotherm fits the equilibrium data as effectively as the Freundlich isotherm. Activated carbon used in this research is Jacobi 2000® derived from bituminous coal. The lab scale inlet volumetric flow is 100 mL/h with different Cr6+ concentration for each run, 20 and 35 ppm respectively. Based on scale-up calculation with Length of Unused Bed (LUB) method, for superficial flow of 400 L.m-2.min-1 and service time of six months, the column dimensions for inlet concentration of 20 ppm are 0.62 m diameter and 2.33 m height with 1.87 m carbon bed depth. Concurrently, a slightly bigger column (0.63 m diameter and 2.37 m height column with 1.89 m carbon bed) is necessary for treating inlet concentration of 35 ppm.